Point-in-time survey of healthcare resource utilization, employment, quality of life and caregiver status by disease severity in patients with schizophrenia in the US. (4th March 2022) - Kadakia, Aditi; Fan, Qi; Shepherd, Jason; Bailey, Hollie; Dembek, Carole; Walker, Chloe; Williams, G. Rhys
Abstract: Objective: The objective of this survey was to assess patient outcomes and caregiver status by disease severity among patients with schizophrenia in the United States. Methods: A point-in-time survey was conducted between July and October 2019 via the Adelphi Schizophrenia Disease Specific Programme. Psychiatrists reported on their next 10 eligible patients with schizophrenia including demographics, disease severity, treatment history and hospitalizations. Patients receiving treatment for schizophrenia were classified as mild, moderate or severe based on disease severity. Regression models adjusted for age, sex and race/ethnicity. Results: Psychiatrists ( n = 124) reported on 435 mild, 401 moderate and 247 severe patients. Greater severity of schizophrenia was associated with a greater number of hospitalizations related to schizophrenia relapse in the previous 12 months (moderate vs. mild: adjusted incidence rate ratio (aIRR) [95% CI] = 2.17 [1.60–2.94]; severe vs. mild: aIRR = 5.45 [3.59–8.27]), lower full-time employment (moderate vs. mild: adjusted odds ratio (aOR) = 0.15 [0.08–0.28]; severe vs. mild: aOR = 0.02 [0.002–0.12]) and greater unemployment due to disability (moderate vs. mild: aOR = 4.24 [3.02–5.97]; severe vs. mild: aOR = 10.85 [6.85–17.17]). Patients with severe vs. mild schizophrenia had lower average quality of life (QoL) measured by the EuroQoL 5-dimension Health Index (difference = −0.16 [−0.23−0.09]). Among patients requiring care, patients with severe vs. mild schizophrenia received more caregiver hours per week (aIRR = 1.89 [1.25–2.84]). Conclusions: Greater severity of schizophrenia was associated with a significantly greater number of hospitalizations and greater unemployment due to disability. Compared with mild schizophrenia, severe schizophrenia was associated with worse patient QoL and greater caregiver hours.